PENGEMBANGAN METODE INKUIRI PADA PEMBELAJARAN PKN KELAS V SEKOLAH DASAR - Asti Islamiati; Erwin Rahayu Saputra (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
In this era, having critical thinking skills is a skill that must be possessed by everyone because it is one of the life skills. However, in reality not everyone has the ability to think critically. So we need an innovation to help train or develop critical thinking skills starting from education in elementary schools. The development of innovation is carried out in one of the lessons, namely Civics in class V Elementary School by involving the inquiry method which aims to train students' critical thinking skills in posing a problem and solving it. This study uses a research and development approach with a class action method. Based on the results obtained that as many as 80% of students are able to pose problems and as many as 70% of students provide solutions to the problems posed. The development of the inquiry method shows students' critical thinking skills in Civics learning with socio-cultural discussions in Indonesia.